Multiplicity of Solutions for a Class of Kirchhoff–Poisson Type Problem - Ziqi Deng; Xilin Dou (Abstract and Applied Analysis)
In this paper, we use the fountain theorems to investigate a class of nonlinear Kirchhoff–Poisson type problem. When the nonlinearity f satisfies the Ambrosetti–Rabinowitz’s 4-superlinearity condition, or under some weaker superlinearity condition, we establish two theorems concerning with the existence of infinitely many solutions.